2012
DOI: 10.1007/s11356-012-1418-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) reduce hepatic β-oxidation of fatty acids in chick embryos

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widespread fused-ring contaminants formed during incomplete combustion of almost all kind of organic materials from both natural and anthropogenic sources. Some PAHs have been shown to be carcinogenic to humans, and a wide range of PAHs are found in wildlife all around the globe including avian species. The purpose of this project was to assess the effects of a standard mixture of 16 PAHs (United States Environmental Protection Agency) on the hepatic fatty acid β-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Although the precise mechanisms by which PAHs affect child development are not confirmed, some mechanisms including endocrine disruption (Westman et al, 2013), binding to human growth factor receptors and aryl hydrocarbon (Ah) receptor to induce P450 enzymes are suggested (Shimada et al, 2013). There are evidences that PAHs may act through disrupting estrogen-mediated pathways (Sievers et al, 2013).…”
Section: Developmental Effects Of Childhood Pah Exposurementioning
confidence: 99%
“…Although the precise mechanisms by which PAHs affect child development are not confirmed, some mechanisms including endocrine disruption (Westman et al, 2013), binding to human growth factor receptors and aryl hydrocarbon (Ah) receptor to induce P450 enzymes are suggested (Shimada et al, 2013). There are evidences that PAHs may act through disrupting estrogen-mediated pathways (Sievers et al, 2013).…”
Section: Developmental Effects Of Childhood Pah Exposurementioning
confidence: 99%
“…Then, through catalysis of carnitine acyltransferase II, acyl-CoA is being recovered within the mitochondrial matrix and directed towards β-oxidation [51] . Recently, Westmann et al showed that fatty acid β-oxidation in chicken embryo liver was significantly reduced in response to the treatment with a mixture of 16 different PAHs [52] . In transgenic mice activation of AHR inhibited hepatic fatty acid β-oxidation along with acyl-CoA oxidase 1, the rate limiting enzyme in peroxisomal β-oxidation [53] .…”
Section: Discussionmentioning
confidence: 99%
“…They enter tissues through inhalation, ingestion, and dermal contact, and their rate of absorption increases when they are present in mixtures. The liver is generally the most important site where toxicants undergo biotransformation (e.g., Westman et al (2013)), but generally most if not all organs are affected to some extent by PAH, with their toxicity dependent upon dose, concentration, time, route of exposure, further distribution, sensitivity, and ability of the organ to metabolize these compounds (Canga et al, 1993).…”
Section: Organic Toxicants As Developmental Disruptorsmentioning
confidence: 99%